Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Matematika - Siregar, Nur Fauziah (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2019)
This study aims to describe errors made by students in solving mathematical problems in the pythagorean theorem material. This research is a descriptive study with the object of research is class VIII-3 of Junior High School (Padangsidimpuan Middle School-7) T.A 2018/2019 which amounted to 21 students with heterogeneous levels of ability. The instrument collects data using essay tests. Data analysis is done by reducing data in the form of paragraphs and images, then drawing conclusions. The results of this study indicate that the common mistakes made by students in this study were more on type-1 errors, namely understanding the concept of errors, followed by type-3 errors, namely units of measurement of writing errors, then followed by type-2. error which is a calculation error, and type-4 error is a mathematical procedure error.